(untitled) (European Journal of Pure and Applied Mathematics, 2018)
How satisfied is each of us with the fulfillment of his life? In this paper after a thorough search of the literature about satisfaction, 58 criteria and subcriteria related to satisfaction or fulfillment were identified and arranged in a hierarchic structure. A process of prioritization known as the Analytic Hierarchy Process is used with the structure, putting in judgments from knowledgeable people to derive priorities for the criteria and subcriteria. A template was then developed for the reader to rate his satisfaction on each of the subcriteria in the structure to obtain an overall measure of satisfaction with their life. Someone who feels they have a perfect life would get 100%. The template can be used by any individual to determine what grade they get in life satisfaction. Readers can get the model to assess the reader’s level of life-satisfaction proposed in this paper at https://1drv.ms/x/s!Ao0b6FaIKSXM_AiH8x7JG5E09QCV.